Recent developments in the chemistry of lithiated epoxides - Hodgson, D; Gras, E (2002)
Although the lithium base-induced β-elimination of epoxides to allylic alcohols is a well-known reaction, α-lithiation has also been described many times. The resulting lithiated epoxides, first postulated as intermediates by Cope in 1951, have been invoked in a wide range of reactions, with their carbenoid properties allowing for very different reactivities. This review covers the recent advances (∼1996 - mid 2002) in the rich chemistry of these main-group metal carbenoids, especially their generation by enantioselective α-deprotonation.